IMPLEMENTATION OF RELIGIOUS CULTURE IN THE FORMATION OF CHARACTER RESPONSIBILITIES OF CLASS IV STUDENTS AT SDN TUNGKULREJO - Permatasari, Intan; Malaikosa, Yes Matheos Lasarus; Susanto, Sofyan (Idaarah: Jurnal Manajemen Pendidikan, 2022)
The purpose of this study is to determine how religious culture is implemented in the process of developing responsible character in fourth grade students at SDN Tungkulrejo. More specifically, this study will focus on implementation, the role that teachers, parents, and society play, as well as the outcomes of religious culture implementation. In this particular piece of research, a qualitative descriptive approach is used. The key information for the research came from the school's administrator, two teachers, three parents, and three students in the fourth grade at SDN Tungkulrejo. Documentation, in-depth interviews, and observation were the primary modes of data collection used to compile the techniques for data collection. The application of religious culture in the formation of a responsible character in the student participants has begun to take shape, which can be determined as one of the conclusions of this study from the data that was obtained after it had been examined. When it comes to implementing aspects of religious culture, however, both instructors and students continue to confront a number of obstacles.